2017
DOI: 10.1364/oe.25.010255
|View full text |Cite
|
Sign up to set email alerts
|

Graphene light modulators working at near-infrared wavelengths

Abstract: Abstract:We demonstrate a graphene-based electro-absorption modulator with extremely small modulation volume that can be controlled by low gating voltages 1-3 V and shows light modulation at wavelengths as short as 900 nm. Our choice of hafnium oxide dielectric separator gives the possibility to obtain significant electro-optical effect in a simple optical heterostructure. Having low power consumption, our devices could find a wide range of applications in telecom industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…i.e., to achieve the same chemical potential μ c in the case of a SiO 2 layer, one needs to apply a voltage 6.4 times higher than that for the HfO 2 layer. In addition, taking into account the supercapacity effect shown for HfO 2 in [20], in a real experiment this difference can be even bigger. However, it is worth of noting that dielectric permittivity of a material chosen for the buffer layer should not be very high due to the fact that this will lead to high remnant polarization, high hysteresis, and long retention times of the buffer layer [29] which, in turn, will lead to a slowdown in operation of the device.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…i.e., to achieve the same chemical potential μ c in the case of a SiO 2 layer, one needs to apply a voltage 6.4 times higher than that for the HfO 2 layer. In addition, taking into account the supercapacity effect shown for HfO 2 in [20], in a real experiment this difference can be even bigger. However, it is worth of noting that dielectric permittivity of a material chosen for the buffer layer should not be very high due to the fact that this will lead to high remnant polarization, high hysteresis, and long retention times of the buffer layer [29] which, in turn, will lead to a slowdown in operation of the device.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, graphene-supported devices have recently been considered as a subject for combining with a relatively well-established research field such as plasmonic biosensors, which also revealed new intriguing features [15]. Additionally, because the graphene layer itself can support different kind of plasmonic resonances, graphene plasmonics has emerged recently as a promising field to further advance the applications [16][17][18][19][20][21][22]. In the present work, we aimed to further increase the actively controlled modulation depth of graphene-based optical modulators/switchers and to simultaneously reduce the applied voltage V g required to achieve maximum modulation values.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that the graphene flake increases the charge induced by a given gating voltage with time (which shifts the CNP voltage further away from the applied voltage position). Hence, one can describe the negative hysteresis of an undoped graphene sample by an increase of the capacitance of the dielectric layer with time, 23 which leads to the formation of a supercapacitor. 24 Alternatively, the negative gating hysteresis of an originally undoped sample could be observed at a fixed applied gate voltage as a decrease of the graphene resistance with time caused by the shift of CNP voltage away from the applied voltage position.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of an additional dielectric layer in a SPR structure can lead to complications connected with large electric fields induced in the layers. In our recent works [21][22][23], we have shown that electric double-layers (or ion traps) at the interfaces of metal-dielectric and dielectricgraphene can be easily formed. Due to this effect, it is possible to enhance the charge induced in graphene and hence to affect its properties.…”
Section: Introductionmentioning
confidence: 99%